The Cambridge history of Christianity / 1 Origins to Constantine / ed. by Margaret M. Mitchell ... - Mitchell, Margaret Mary (The Cambridge history of Christianity, 2006)
The first of the nine volume Cambridge History of Christianity series, Origins to Constantine provides a comprehensive overview of the essential events, persons, places and issues involved in the emergence of the Christian religion in the Mediterranean world in the first three centuries. Over thirty essays written by scholarly experts trace this dynamic history from the time of Jesus through to the rise of Imperial Christianity in the fourth century. It provides thoughtful and well-documented analyses of the diverse forms of Christian community, identity and practice that arose within decades of Jesus's death, and which through missionary efforts were soon implanted throughout the Roman Empire. Origins to Constantine examines the distinctive characteristics of Christian groups in each geographical region up to the end of the third century, while also exploring the development of the institutional forms, intellectual practices and theological formulations that would mark Christian history in subsequent centuries
Keywords: Aufsatzsammlung; Römisches Reich; Kirche; Frühchristentum; Theologie; Verbreitung; Gemeinschaftsgefühl; Gruppenidentität; Entwicklung; Geschichte 30-313; Religion; Gesellschaft; Politik; Christentum